Pharyngitis and Tonsillitis, Diphtheria, Infectious mononucleosis and general principles of antibiotic therapy in children - Usachova, O. V.; Konakova, O. V.; Усачова, Олена Віталіївна; Конакова, Ольга Володимирівна (Запорізький державний медичний університет, 2013)
This manual addresses vaccination, historical, epidemiological and sociocultural issues as well as clinical and molecular biological aspects of tonsillitis.